A visit from the Goon Squad [large type] - Egan, Jennifer (Thorndike Press large print basic, 2011)
Jennifer Egan's spellbinding interlocking narratives circle the lives of Bennie Salazar, an aging former punk rocker and record executive, and Sasha, the passionate, troubled young woman he employs. Although Bennie and Sasha never discover each other's pasts, the reader does, in intimate detail, along with the secret lives of a host of other characters whose paths intersect with theirs.